PENGARUH MOTIVASI BELANJA HEDONIS, UANG SAKU DAN PROMO DISKON TERHADAP PEMBELIAN IMPULSIF MAHASISWA JURUSAN MANAJEMEN UNIVERSITAS ISLAM NEGERI SUMATERA UTARA PADA APLIKASI SHOPEE - Muhammad Arif; Nursantri Yanti; Vania Sally Nabila (Jurnal Ekonomi Manajemen dan Bisnis, 2023)
This study aims to determine the effect of hedonic shopping motivation, pocket money and discount promos on impulse purchases of students majoring in management at the State Islamic University of North Sumatra on the Shopee application. This research was conducted on all active management students of the State Islamic University of North Sumatra with a population of 844 students and a sample of 89 students. The sampling technique in this study uses a probability sampling approach using random sampling, namely random sampling. This study used primary data obtained using questionnaires. The data analysis techniques used in this study are descriptive statistical tests, classical assumption tests, multiple linear regression analysis and hypothesis tests. The results proved that hedonic shopping motivation, pocket money and discount promos had a positive and significant effect on the impulse purchases of students majoring in management at the State Islamic University of North Sumatra on the Shopee application.